Tourism Management Guidelines for Huay Nam Sai Village, Suan Phueng District, Ratchaburi Provinc - Meekrut, Prunnika; Kuntasen, Sopa (Journal of Humanities and Social Sciences, Rajapruk University, 2024)
ABSTRACT The Objective of this research was to study 1) the problems of tourism management, 2) analyze the internal and external situations of tourism management, and 3) propose a guideline for tourism management in Mon Huai Nam Sai Village, Village, Suan Phueng District, Ratchaburi Province This research was qualitative research methodology by studying research documents, participatory observation, in-depth interview and brainstorming. The sample was 21 people compound with the village committee of Mon Huai Nam Sai, restaurant business operator, accommodation business operators, merchandise and souvenir business operators, and villagers by purposive sampling. The results of the research revealed that 1) Problems of Huai Nam Sai village tourism management in terms of administration, it was found that government agencies not take part in the administration. In terms of basic utilities, it was found that there were only 3 service points for toilets. It was found that the government not come to support any budget and public relations. It was found that the government not come to support or help publicize. 2) SWOT Analysis found that; 2.1) Strengths (S): The community has abundant natural resources. 2.2) Weaknesses (W): The tourist guide personnel is insufficient. 2.3) Opportunities (O): There is a tendency to have more tourists coming to travel. 2.4) Treat (T) lack of budget for the development of tourist attractions from the government. And 3) Guidelines for tourism management in Mon Huai Nam Sai Village, consisting of (a) implementation of measures to control and prevent the spread of the COVID-19 virus (b) public relations for tourism in Mon Huai Nam Sai Village through various media that reach more tourists with current media; (c) supporting the creation of community shops for people in the community to earn income; (d) integrating cooperation with government agencies to develop tourism; and (e) making signs to guide the way to facilitate tourists.